A study on antidiabetic, and antibacterial activities of Leea rubra Blume - Do, Van Mai; Le, Truong Han; Ngo, Hong Phong; Phung, Phat Nguyen; Mai, Van Hung (International Journal of Innovative Research and Scientific Studies, 2025)
The current work investigated the antioxidant, antibacterial, and antidiabetic properties of extracts from Leea rubra roots, stems, and leaves in vitro. The antioxidant capabilities of Leea rubra extracts were tested using 2,2-diphenyl-1-picryl-hydrazyl, 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid), nitric oxide, total antioxidant activity, ferric reducing-antioxidant power, and reducing power tests. The extracts' antibacterial activity against Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli was tested using the agar-well diffusion method. The antidiabetic efficacy of the extract was assessed by inhibiting α-amylase and α-glucosidase. Leea rubra extracts have shown strong antioxidant and antidiabetic action, with IC50 values ranging from 6.63 (0.05 to 27.49 (0.64 µg/mL and 20.31 (0.46 to 41.84 (0.02 µg/mL, respectively. Leea rubra extracts demonstrated significant antibacterial activity, with minimum inhibitory concentrations ranging from 160 to 640 µg/mL. Furthermore, the chemical composition study revealed the existence of alkaloids, polyphenols, flavonoids, steroids, tannins, saponins, and glycosides. This study reveals that Leea rubra contains a high potential for natural antibacterial, antioxidant, and antidiabetic properties.